Regional learning levels of Tourism business development (Innovative aspect). (Economics and region, 2017)
UDC 338.482.2 Komelina Olha, Doctor of Economics, Professor. Shamila Hassan Ismail, graduate student. Poltava National Technical Yuri Kondratyuk University. Regional learning levels of Tourism business development (Innovative aspect). In the article features of the organization of tourist business in Ukraine and its regions are considered. The factors of international competitiveness of tourist activity in Ukraine are analyzed. Investigated entrepreneurial activity in the field of tourist services in the regions of Ukraine in 2016. The place and role of the tourist business in Ukraine in the world economy is established. Organizational and economic problems are established to ensure the development of tourism business in Ukraine. The new factors of development of tourist business in the region are substantiated: objects of transport infrastructure, creative potential of territories (cultural, natural, economic, investment, etc.); development of social and inclusive tourism; introduction of new information and communication technologies of international level on recommendations of UNWTO. The levers of increasing the innovative activity of the tourist business in the region are proposed: development of innovative partnership; activation of organizational and marketing innovations; innovations in business education; development of innovation infrastructure; optimization of the structure of the regional tourist product; creation of regional information platforms; implementation of service innovations.